2015
DOI: 10.1684/epd.2015.0782
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of lacosamide as an adjunctive therapy for refractory focal epilepsy in paediatric patients: a retrospective single‐centre study

Abstract: Aim. Lacosamide is an antiepileptic drug approved for the treatment of focal epilepsy in adult patients. The aim of this observational study was to review our centre's experience with lacosamide and to characterize its effectiveness and tolerability as an adjunctive antiepileptic drug in a retrospective cohort of children with refractory focal epilepsy. Methods. We retrospectively reviewed the medical records of 22 patients who received lacosamide from November 2009 to April 2014 at the CHU Ste‐Justine, Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
1
11
0
1
Order By: Relevance
“…Although achieving seizure control produces a secondary positive impact on cognitive and behavioral functioning in children and adolescents, some authors consider lacosamide has a specific primary cognitive enhancing effect improving information processing speed [45]. By contrast, several articles have reported cases of mild negative mood and behavioral changes (5-25%) [18,10,15,13,26,46,12]. In few special cases, lacosamide was discontinued because of severe hyperactivity, aggression, and inattention [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…Although achieving seizure control produces a secondary positive impact on cognitive and behavioral functioning in children and adolescents, some authors consider lacosamide has a specific primary cognitive enhancing effect improving information processing speed [45]. By contrast, several articles have reported cases of mild negative mood and behavioral changes (5-25%) [18,10,15,13,26,46,12]. In few special cases, lacosamide was discontinued because of severe hyperactivity, aggression, and inattention [8,21].…”
Section: Discussionmentioning
confidence: 99%
“…An open‐label study to determine safety, tolerability, and efficacy of oral LCM in children with epilepsy (clinicaltrials.gov identifier NCT00938912) is being conducted in children 1 month to 17 years of age, but the study has not yet been completed. A number of observational studies on the off‐label use of LCM as a maintenance AED in children has been reported (see Table ), but have the limitations of short follow‐up times, variable or unspecified time points for efficacy assessment, small sample sizes, and the retrospective use of the 50% responder rate outcome measure.…”
Section: Discussionmentioning
confidence: 99%
“…1012 The use of adjunctive lacosamide in children and adolescents has been investigated in open-label trials 13,14 and reported in observational studies. 1520 The objective of this randomized, double-blind, placebo-controlled trial was to evaluate the efficacy and tolerability of adjunctive lacosamide in children and adolescents (≥4–<17 years of age) with uncontrolled focal seizures.…”
mentioning
confidence: 99%